PENGEMBANGAN LKPD BERBASIS EXPLORING, CLUSTERING, SIMULATING, VALUING, AND EVALUATING PADA TEMA KESELAMATAN DI RUMAH DAN PERJALANAN DI KELAS II SD - Riska Aprillia; Safrida Napitupulu (Jurnal Cakrawala Ilmiah, 2025)
This study aims to: (1) To find out the feasibility of LKPD based on Exploring, Clustering, Simulating, Valuing, and Evaluating on the Theme of Safety at Home and Travel in Grade II of Elementary School. This research is a type of development research (Research and Development) using the ADDIE development model which includes five stages, namely: Analysis, Design, Development, Implementation, and Evaluation. However, this research only goes up to three stages, namely only up to the Development stage. The subjects in this study were validators of material experts, language experts, learning experts (responses of grade II teachers). The instrument used to collect data was a questionnaire. The data analysis technique used was a qualitative descriptive analysis technique. The media developed was validated by one material expert, one language expert and one grade II elementary school teacher. Based on the assessment of the validation results by the material expert, the LKPD product was produced which was feasible for use by grade II elementary school students. Based on the assessment of the validation results by language experts, it produces a LKPD product that is very suitable for use by grade II elementary school students and based on the assessment of the validation results by learning experts, it produces a LKPD product that is very suitable for use by grade II elementary school students. So from the validation data from the three validators, it can be concluded that the LKPD media Based on Exploring, Clustering, Simulating, Valuing, and Evaluating on the Theme of Safety at Home and Travel in Grade II Elementary School is declared valid and there is no revision by the experts, so it is declared very suitable for use as teaching materials in learning